2021
DOI: 10.1021/acssuschemeng.1c06401
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonic Acid-Functionalized Zeolite Beta: Bronsted Acid Catalysts for Reactions Involving Liquid Water

Abstract: The utility of zeolites in biomass upgrading reactions can be limited in cases where stronger Bronsted acidity and/or hydrophobicity are required for effective catalysis. While sulfonated solids/sulfonic acid catalysts can be used in such cases, they forego the advantageous effects of confinement that are afforded by zeolites. Here, acidity, hydrophobicity, and confinement are integrated into a solid material by functionalizing the intrapore voids of zeolite Beta with phenethyl-sulfonic acid sites (PE-Betas). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…45 The benzene ring of SA also promoted the hydrophobicity of the catalyst, which enabled 4-MOPE to successfully carry out the next dehydration reaction. 32 In addition, the prepared catalyst can completely convert the substrate and the carbon balance can reach more than 95%. As shown in entry 3 of Table 3, PSA–Hf (2 : 1 : 0.5) had the best proportion of PA, SA, and HfCl 4 , showing the best catalytic activity (97.2% AN yield) and TOF (9.3 h −1 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…45 The benzene ring of SA also promoted the hydrophobicity of the catalyst, which enabled 4-MOPE to successfully carry out the next dehydration reaction. 32 In addition, the prepared catalyst can completely convert the substrate and the carbon balance can reach more than 95%. As shown in entry 3 of Table 3, PSA–Hf (2 : 1 : 0.5) had the best proportion of PA, SA, and HfCl 4 , showing the best catalytic activity (97.2% AN yield) and TOF (9.3 h −1 ).…”
Section: Resultsmentioning
confidence: 98%
“…31 The signals at 1140 and 1235 cm −1 represented the symmetric and asymmetric stretching vibrations of OvSvO, respectively. 32 There was a blueshift in the stretching vibrations of S-O, from 758 cm −1 (SA) to 812 cm −1 (PAS-Hf (2 : 1 : 0.5)). This can explain the extreme bridging connection between the Hf and -SO 3 groups.…”
Section: Catalyst Characterizationmentioning
confidence: 95%
“…31,32,67 Davis and co-workers have recently shown that grafting phenethyl-sulfonic acid sites into the micropores of the wide pore zeolite H-beta gives a very efficient catalyst for the hydroxyalkylation/alkylation condensation reaction of 2-methylfuran with acetone. 24 This increased catalytic efficiency results from the confinement effect of the zeolite micropores, combined with increased hydrophobicity imparted by the grafting sulfonic acid containing residues into silica-rich micropores. The grafted sulfonic acid contains an aromatic ring and a linking alkyl chain, with a reactive sulfonic acid head-group placed on the aromatic ring.…”
Section: Discussionmentioning
confidence: 99%
“…25,26,62 Davis and co-workers have recently shown that grafting phenethyl-sulfonic acid sites into the micropores of the wide pore zeolite H-beta gives a very efficient catalyst for the hydroxyalkylation/alkylation condensation reaction of 2-methylfuran with acetone. 23 This increased catalytic efficiency results from the confinement effect of the zeolite micropores, combined with increased hydrophobicity imparted by the grafting sulfonic acid containing residues into silica-rich micropores. The grafted sulfonic acid contains an aromatic ring and a linking alkyl chain, with a reactive sulfonic acid head-group placed on the aromatic ring.…”
Section: Discussionmentioning
confidence: 99%